Integrated Pest Management (IPM) Environmentally Sound Pest Management - Kaur Gill, Harsimran; Goyal, Gaurav (IntechOpen, 2016)
This book is an update on environmentally sound pest management practices under the umbrella of integrated pest management (IPM). It consists of seven contributions from different authors providing information on pest management approaches as chemical alternatives. The book chapters detail about historical review of IPM concepts; strategies and some experiences in applications of IPM in Latin America; pest control in organic agricultural system; and the use of entomopathogenic and molluscoparasitic nematodes, insect pheromones, semiochemicals, detergents, and soaps as a part of IPM scheme. The goal of this book is to provide the most up-to-date review on information available around chemical alternatives in IPM. Therefore, this book will equip academia and industry with adequate basic concepts and applications of IPM as eco-friendly pest management option.